Ascorbic acid-containing compound efficacy in ischemic brain damage - Rita M. Termulaeva; Konstantin Y. Belanov; Natalya D. Bunyatyan; Aleksander S. Pirozhkov; Dmitrii E. Timoshkin; Ekaterina V. Blinova; Olga V. Vasilkina; Kirill D. Blinov; Elena V. Semeleva; Aleksander A. Dmitriev; Dmitrii S. Blinov (Research Results in Pharmacology)
Introduction: Ischemic brain injury remains one of the main causes of disability and mortality worldwide. Protection of cellular population, depriving from oxygen supply and nutrients, is of extreme importance for further both clinical and health outcomes of timely implemented intravascular intervention. The aim: to assess anti-ischemic activity of 3-hydroxypyridine ascorbate in the in vitro and in vivo models of brain cell and tissue response to ischemia and reoxygenation.